Efeito leishmanicida e cicatrizante da pomada de Dysphania ambrosiodies (L.) Mosyakin & Clement em lesões causadas por Leishamnia (Leishmania) amazonensis - GODINHO, Andressa de Souza da Silva (2019)
Leishmaniasis are diseases with a high incidence and wide geographical distribution. They also have a wide spectrum of clinical manifestations, related to the species of parasite that causes the disease. Among these clinical manifestations are local skin lesions caused by the species Leishmania amazonensis. The treatment of leishmaniasis involves drugs and other therapies, however the most used drugs have limitations to their use, such as protozoan resistance, high toxicity and the inconvenience of local pain, generating rejection and interruption of the use of these drugs by patients. This problem has contributed to the increase in government investments and aroused interest in research for viable therapeutic alternatives, such as pharmacological investigation of plant species. The plant species Dysphania ambrosioides already has some properties described in the literature as repellent, bactericide, insecticide, antitumor, anti-inflammatory, wound healing and leishmanicidal. Based on this and aiming at the formulation of a drug based on plant extract, our objective was to evaluate the topical treatment with D. ambrosioides ointment at 25% in lesions caused by Leishmania amazonensis in an animal model, as well as to investigate in vitro the mechanism of action of the extract on the parasite. The extract from the leaves of D. ambrosioides was added to an ointment based of lanolin and petroleum jelly. After the manipulation of the ointment, physical-chemical tests, pH measurement and determination of sensory characteristics were performed to evaluate the preliminary and accelerated stability. For the control of microbiological quality, the counting of viable and pathogenic microorganisms and Gram staining were carried out in colonies isolated from the plant extract and the manipulated ointment. The results showed that the samples had no significant changes between the parameters evaluated above, being suitable for use in in vivo models. For the in vivo trial, Balb/c mice received a subcutaneous inoculum of 5x105 L. amazonensis stationary promastigotes in the right ear. At the 5th week after infection, the animals were separated into four groups of 10 animals, named: Negative control (CN) treated with 0.1mL of the ointment excipient for 28 days, experimental (DA) treated with 0.1mL of the D. ambrosioides ointment for 28 days, Positive control (AM) which received the pentavalent antimonial (28 mg/kg/day) for 15 days and the group that received an association of the compounds (DAAM) was treated simultaneously with D. ambrosioides ointment for 28 days and pentavalent antimonial (Sb+5) (28 mg/ kg/day) intraperitoneally for 15 days. Parameters such as the lesion area, parasitic load, cellularity of the lymphoid organs, cell immunophenotyping of the cervical lymph node, spleen, peritoneum and lesion, production of cytokines, production of nitric oxide and action of the extract directly on the parasite were evaluated. Animals treated with D. ambrosioides ointment showed a reduction in the lesion area, in addition to a reduction in parasitic load. This treatment also induced the production of peritoneal nitric oxide and increased production of inflammatory and regulatory cytokines. Moreover, a population of CD4+ T lymphocytes was detected in the spleen and lymph node, in addition to a population of macrophages activated in the lesion, characterizing the importance of these cells in the course of the disease. Therefore, the D. ambrosioides ointment ratified the results regarding the inflammatory and immunomodulatory capacity of the crude D. ambrosioides extract from the increase in inflammatory and regulatory cytokines, increased macrophages activated at the injury site, characterizing a potential healing effect, with tissue remodeling, thus reducing the treated lesion area.